Optimization of antibody-conjugated magnetic nanoparticles for target preconcentration and immunoassays - Smith, Joshua E. (2010)
Biosensors based on antibody recognition have a wide range of monitoring applications that apply to clinical, environmental, homeland security, and food problems. In an effort to improve the limit of detection of the Naval Research Laboratory (NRL) Array Biosensor, magnetic nanoparticles (MNPs) were designed and tested using a fluorescence-based array biosensor. The MNPs were coated with the fluorescently labeled protein, AlexaFluor647–chicken IgG (Alexa647–chick IgG). Antibody-labeled MNPs (Alexa647–chick–MNPs) were used to preconcentrate the target via magnetic separation and as the tracer to demonstrate binding to slides modified with anti-chicken IgG as a capture agent. A full optimization study of the antibody-modified MNPs and their use in the biosensor was performed. This investigation looked at the Alexa647–chick–MNP composition, MNP surface modifications, target preconcentration conditions, and the effect that magnetic extraction has on the Alexa647–chick–MNP binding with the array surface. The results demonstrate the impact of magnetic extraction using the MNPs labeled with fluorescent proteins both for target preconcentration and for subsequent integration into immunoassays performed under flow conditions for enhanced signal generation.